Brassica Oleracea VAR. Capitata Efektif Mengatasi Engorgement: Sebuah Review Sistematis - Marella Marella; Rita Ridayani; Ristina Rosauli Harianja; Nurniati Tianastia Rullyni; Vina Jayanti (COMSERVA : Jurnal Penelitian dan Pengabdian Masyarakat, 2023)
90% of postpartum mothers who breastfeed their babies have increased engorgement. Many studies claim the cabbage (Brassica Oleracea var Capitata) that compressed on the breast which can reduce swelling and pain. This study tried to study the effect of leaf compresses on breast swelling in postpartum mothers. The research design was used with a narrative review of 3 scientific research articles resulting from quantitative research in accordance with the research objectives. The existence of this research is expected to provide appropriate assistance for breast swelling in postpartum mothers.